(untitled) (Revista Electrónica REDINE, 2026)
This research aims to propose a model of non-formal environmental education (NFEE) focused on the sustainable management of municipal solid waste (MSW) in organized communities, in response to the need to articulate educational strategies to promote citizen participation, the development of socio-environmental competencies, and collective commitment to urban sustainability. The methodology was presented under the interpretive paradigm with a hermeneutic approach, a qualitative focus, and a documentary design, centered on the identification, analysis, and interpretation of relevant secondary sources. The study population consisted of scientific and technical literature published between 2020 and 2025 related to NFEE strategies aimed at the sustainable management of MSW. The sample was purposive, considering criteria of content, relevance, quality, time, and language. The results showed that the most frequently applied NFEE strategies are training workshops, educational resources, environmental awareness campaigns, recreational activities, and environmental brigades. These studies demonstrate a positive impact on transforming attitudes and behaviors toward municipal solid waste (MSW) management; however, a systemic approach is required. Therefore, as a final product, an educational model was designed, structured around three pillars (citizen participation, pedagogical design, and institutional support), adaptable to different territorial contexts to strengthen environmental awareness and responsible MSW management. Consequently, the adoption of this model by local governments and organized communities is recommended as a fundamental political and educational tool. Furthermore, the development of future longitudinal research to evaluate its real impact on transforming attitudes and behaviors toward sustainability is encouraged.